Herramienta auxiliar de carga para materiales de la construcción (2022)
In order to solve the need that light-duty builders have today in terms of transferring materials with large dimensions, which at the time of transferring but a single person, the task become tedious an complex, and even more so when there are several units to be transferred, the proposed tool is made up or two lateral crossbars, two 22- gauge sheets which will adjust the materials regardless of the amount is intended to be transferred, these sheets will be supported an transferred thanks to two unidirectional anti.puncture tires. Which support around 150 kg per load regardless of the amount of transfer, the implementation of this tool will help minimize efforts since all the weight of the materials will be supported by the tool and the risk of poor posture or overweight load performed by the operator will be drastically reduced at the same time as the transfer time or thus benefiting both the operator and the progress of the work Within the economic scope of the elaboration of this tool, there is a standard budget which can vary with respect to the inflation of the dollar and the scarcity of the raw material that is required for the elaboration of said element, with the course of the investigation. All the variables that can influence the creation of the company are identified, and sustain it at the it at the end of the first year, making a projection of units that must be sold, monthly, semi-annually and annually, thus relating the legal expenses of each one. Of the workers who will be part of the company and regarding the administrative and operational part. During the development on the investigation and as progress was made on it, the even more notorious absence of the lack of the indicated and qualified tools for the activities related to the transfer of material was demonstrated, the elements existing today and although the advance technology advances greatly, these are still traditional and inefficient in team of different materials such as Drywall sheets, large- area glass, fiber mineral tiles, super board and zing tildes the transfer activities of these materials by custom and tradition it has been carried out jointly by two or more people and that is very important point that as a research group it is contemplated to make the tool that can reduce and minimize transfer time and in teams of the human factor in relation to the physical effort that must be made to carry out these activities reduce said forces improve the body health operary The information embodied within this research has been collectively, with the members of this project where each one from their experience contributes significantly to each of the items treated making relevance in terms of the execution costs of both the product and the creation of a company at the national level governed by the regulations that guide each of the processes necessary to carry out the culmination of the auxiliary loading tool